2016
DOI: 10.3390/rs8080640
|View full text |Cite
|
Sign up to set email alerts
|

First Experiences in Mapping Lake Water Quality Parameters with Sentinel-2 MSI Imagery

Abstract: Abstract:The importance of lakes and reservoirs leads to the high need for monitoring lake water quality both at local and global scales. The aim of the study was to test suitability of Sentinel-2 Multispectral Imager's (MSI) data for mapping different lake water quality parameters. In situ data of chlorophyll a (Chl a), water color, colored dissolved organic matter (CDOM) and dissolved organic carbon (DOC) from nine small and two large lakes were compared with band ratio algorithms derived from Sentinel-2 Lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
276
2
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 398 publications
(309 citation statements)
references
References 43 publications
18
276
2
13
Order By: Relevance
“…Other algorithms could have been used. Besides the Gons et al (2005) method, various approaches were previously developed for turbid and/or eutrophic coastal and inland waters, including the 2-, and 3-band models (Dall'Olmo et al, 2005;Gitelson et al, 2008;Le et al, 2013), the fluorescence line height (FLH, Gower et al, 1999), the maximum chlorophyll index (MCI, Gower et al, 2005), and the 705 nm peak height (Toming et al, 2016). These algorithms are all based on a NIR/red edge either associated with chl a absorption at 675 nm or with sun-induced chl a fluorescence.…”
Section: Discussion Chl a Algorithms In Turbid Coastal Watersmentioning
confidence: 99%
See 1 more Smart Citation
“…Other algorithms could have been used. Besides the Gons et al (2005) method, various approaches were previously developed for turbid and/or eutrophic coastal and inland waters, including the 2-, and 3-band models (Dall'Olmo et al, 2005;Gitelson et al, 2008;Le et al, 2013), the fluorescence line height (FLH, Gower et al, 1999), the maximum chlorophyll index (MCI, Gower et al, 2005), and the 705 nm peak height (Toming et al, 2016). These algorithms are all based on a NIR/red edge either associated with chl a absorption at 675 nm or with sun-induced chl a fluorescence.…”
Section: Discussion Chl a Algorithms In Turbid Coastal Watersmentioning
confidence: 99%
“…Chlorophyll a Algorithm Several algorithms are available for Sentinel2/MSI (Beck et al, 2016;Toming et al, 2016) to retrieve chl a concentration from ρ w (λ) in coastal waters. For our study site, an intercomparison exercise based on in situ measurements demonstrates that the chlorophyll-retrieval algorithm of Gons et al (2005) provided the most satisfactory results (see Supplementary Information for more details).…”
Section: Bio-optical Algorithmsmentioning
confidence: 99%
“…which affects the atmospheric correction accuracy of Sen2Cor algorithm. Toming et al [12] found the shape similarity of MSI-corrected dataset using the Sen2Cor algorithm compared with a historical dataset (2011)(2012)(2013), although the MSI reflectance spectra were overestimated by the algorithm. In the Amazon context, the presence of forest surfaces benefits AOD retrievals by the Sen2Cor algorithm, however, this surface neighbour also implies in severe adjacency contamination on the water spectrum measured by orbital sensors.…”
Section: Inter-comparison Of Atmospheric Correction Methodsmentioning
confidence: 99%
“…1). S2A, launched on 23 June 2015, has been already used for the assessment of water constituents, for example, in the oligotrophic waters of Starnberg Lake and in the humic lakes (Toming et al, 2016). Moreover, the MSI bands close to the red-edge are promising for resolving productive turbid waters.…”
Section: Introductionmentioning
confidence: 99%